Evaluation of the elasticity of yarns in fabrics analysis of the work carried out on (Texas Journal of Engineering and Technology, 2022)
In this article, the optimal strength of the three factors to maximize the penetration of the surface location. and it was determined that the supported surface is observed during the descent.